Individualization and Marketization of Responsibility for Gender Equality: The Case of Female Managers in China. Issue 3 (19th January 2016) - Tatli, Ahu; Ozturk, Mustafa Bilgehan; Woo, Hong Seng
Abstract: This article investigates the question of where the responsibility for promoting gender equality resides in the Chinese employment context. Utilizing Acker's (2006) inequality regimes framework, the study explores women's underrepresentation in management roles in China and explains the persistence of gender inequalities in managerial echelons of Chinese organizations. Based on 30 interviews with female managers, the findings demonstrate the marketization and individualization of gender equality in organizational activity. The existing gender inequality, and the lack of responsibility for tackling it, has been either legitimized by eluding to the commercial‐only focus of organizations or rendered invisible through a belief in individual choice as the determining factor of career progression for women. Gender inequality in management is also maintained through the compliance of female managers themselves with the presumed legitimacy of gender‐based differential access to managerial roles. References to culture and tradition, market forces, competitive pressures, and individual choices by female managers are often made in explaining the unequal career paths and outcomes for men and women in their organizations. Our findings contribute to the human resource management (HRM) literature by framing macrosocietal context as a dynamic and endogenous aspect of management of human resources in organizations and provide novel insights into the interplay between HRM and societal context. © 2016 Wiley Periodicals, Inc.